Pengaruh Promosi Melalui Media Instagram, Kualitas Produk, Dan Harga Terhadap Keputusan Pembelian Brand Erigo (Studi Kasus Pada Konsumen Erigo Kecamatan Tajinan Malang) - Alfan Prakhas Pratama; Budi Wahono; Nanik Wahyuningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research aimed to identify the effect of promotion via Instagram, product quality, and price on purchasing decisions. The independent variables used are promotion via Instagram, product quality, and price, while the dependent variable is the purchase decision. The sample used in this study were 96 respondents who were Erigo consumers in Tajinan Malang District. The data collected using a questionnaire. The analysis method using a instrument test, multiple linear regression analysis, classical assumption test, determination test, f test and t test using the help of SPSS 25.0 computer software. The results of this study indicate that promotion via Instagram has a significant positive effect on purchasing decisions, product quality has a significant positive effect on purchasing decisions, price has a significant positive effect on purchasing decisions, and promotion via Instagram, product quality, and price simultaneously have a significant positive affect on purchasing decisions. Keyword: promotion via Instagram, product quality, price, and purchasing decisions